MINORITY RIGHTS FIGHTER IN THE LITERATURE: RESEARCH IN THE NOVELS SEJUTA DOA UNTUK GUS DUR BY DAMIEN DEMATRA - Wawan Hermawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
Discrimination against the rights of minorities must be avoided by the majority group by prioritizing the views, attitudes and behaviors that respect, accept and acknowledge all differences. The focus of this study describes the figure of Abdurahman Wahid who defended and fought for the rights of minorities contained in the novels Sejuta Doa untuk Gus Dur by Damien Dematra.This research is a type of qualitative research, with content analysis data analysis techniques. The research data are sourced from the novel A Million Prayers for Gus Dur by Damien Dematra in the form of Abdurahman Wahid's defense or struggle against minorities. Data collection techniques using the technique of reading and taking notes. Data validation uses theory triangulation. The findings show Abdurahman Wahid's defense and struggle against minority rights. Gus Dur's struggle in viewing minority rights can be seen from the thoughts, attitudes and actions of Gus Dur who care for minorities who experience discrimination and violence. Gus Dur's consistency in defense for minority rights has implications for harmony between religious communities.The results of this study can be useful for society as a reflection of living in harmony, which can respect a difference. In addition, for lecturers, teachers, and student the results of this study are useful as an alternative to learning literature at schools and universities from a multicultural value perspective. This study examines Gus Dur's attitudes, views and behavior in defense for minority rights. Respect for minority rights is a form of living in harmony. Gus Dur's struggle and consistency in defending the rights of minorities should be practiced by every citizen by respecting, accepting and acknowledging all the differences. Keywords: discrimination, minority, struggle, Gus Dur